Pembangunan Sistem Informasi E-Canteen Berbasis Web Mobile di Politeknik Statistika STIS - Erik Rihendri Candra Adifa; Ibnu Santoso (Seminar Nasional Official Statistics, 2022)
Common problems found in the STIS Statistics Polytechnic canteen include long queue waiting times, limited food stock availability, and the need for accurate sales recapitulation. The direction for digitizing MSMEs by the government provides an opportunity for the STIS Statistics Polytechnic to change the canteen system to be digitized. The system built allows shoppers to find out information on menu availability and place an order for a meal menu before arriving at the canteen. Buyers can also provide ratings and suggestions as or evaluation. From the seller's point of view, they also benefit from automatic recapitulation and sales statistics. The system development method used is the System Development Life Cycle (SDLC) Waterfall approach. The results of the Black Box test show that all functions are expected to run well. The score of the System Usability Scale (SUS) test result is 74.64 which indicates that the E-Canteen information system is well received. The results of the Post-Study System Usability Questionnaire (PSSUQ) test also showed good results.